A Critique of Charles Taylor’s Theory of Recognition - Peter Piringkwap Maigari (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
This paper seeks to appraise Charles Taylor's theory of recognition which revolves around equal dignity, the ideal of authenticity and the fusion of horizons. This paper found out that Taylor's theory holds that our individual identity is shaped by recognition or its absence. Hence, a person or group of people can suffer real imagery damage or the distortion of the same if the people or society hold a distorted and demeaning image of them to the extent that misrecognition on the one hand or non-recognition, on the other hand, can both inflict psychological harm and distort their mode of being. In this paper, I argue that Taylor's theory of recognition, as plausible as it seems, is flawed. The conclusion that is reached therefore is that Taylor's three modes of recognition is inadequate in the formation of a multicultural society that will guarantee tolerance and peaceful authentic existence in the society.